Thuật toán nhận dạng thích nghi các đối tượng trong hệ thị giác máy - Tao, Ngo Quoc; Kiem, Hoang (Journal of Computer Science and Cybernetics, 2018)
In this paper, we present adaptive recognition algorithm for visition systems. Our method is divided into following principal steps: -Determine the minimum number of feature for object recognition. -Graphical matching. -Object recognition. -Statical evalution. The experimental results are presented also.